Referendum as a Legal Tools for Achieving Self-Determination: The Case of Kurdistan Region, Iraq - Qader, Sanh Sharif (Globeedu Group, 2019)
Referendums on the right to achieve self-determination has become a significant tool used in attaining collective political, economic, social and cultural aspiration since the decolonization era. On 25 September 2017, the people in the Kurdish controlled area of Iraq decided overwhelmingly to submit a Referendum to attain self-determination. This paper seeks to examine the use of referendum as a legal tool to achieve self-determination. The literature on the use of referendum as a tool for attaining the goal has been scarce. The Kurdistan Region of Iraq, like its counterparts in other countries, has long been in the struggle to have their own sovereign state. The paper explores and utilizes secondary source materials to cross-examine arguments and draw conclusions. It is found that referendum is an acceptable tool for achieving self-determination as demonstrated in many similar situations across the world. Submissions from our findings will impact meaningfully on the Iraqi government policymaking, the KRG and the international community. It will also add to the pool of existing works on the subject matter